The knowledge of selected cancer prevention methods among Polish outpatients - Kurczewska-Michalak, Marta; Kardas, Przemysław (Family Medicine & Primary Care Review, 2017)
Background . Most prevalent cancers are, in their majority, not fully preventable. However, early diagnosis dramatically increases the chances for effective treatment and positive prognosis. Unfortunately, patients’ participation in relevant screening activities is far from desirable. Taking into consideration the increasing incidence of cancer and mortality in Poland, a higher uptake of these programs is advisable. Objectives . The purpose of this study was to assess the knowledge of selected cancer prevention methods among Polish outpatients. Material and methods. This was a survey involving Polish primary care patients. The study was based on an original questionnaire designed for this purpose and was distributed among primary care patients in either hardcopy (among primary care patients in the urban settings of the city of Lodz) or over the Internet. Results . Sources of information on national cancer screening programs provided by the survey participants significantly correlated with gender, age and education level. Women tended to be significantly more interested in current or future participation in the colorectal screening program than men (46.7% vs 32.3%; p < 0.05). The majority of women were well informed about screening tests concerning breast and cervical cancer (78.2%). The period of time between cervical cancer screenings significantly correlated with the level of education (p < 0.05). Conclusions . 1. Television and press are the most common sources of information regarding national cancer screening programs. 2. Women were more interested in participation in colorectal screening than men. 3. Lack of availability of screening tests proved to be the most common reason for delay in cancer diagnosis provided by respondents.